ANTIOXIDANT ACTIVITY AND TOXICITY OF THE ETHYL ACETATE AND DICHLOROMETHANE FRACTIONS OF THE ETHANOL EXTRACT OF SIKKAM LEAVES (Bischofia javanica Blume) - Putu Widiari; I Wayan Muderawan; Rachmadhani Rachmadhani (Indonesian Journal of Chemistry and Environment, 2026)
Sikkam (Bischofia javanica Blume) is traditionally used to treat sore throat, infected wounds, boils, and diabetes, but scientific evidence remains limited. This study aimed to determine the antioxidant activity and toxicity of the ethyl acetate and dichloromethane fractions of sikkam leaf ethanol extract obtained by maceration. Antioxidant activity was assessed using the DPPH method, and toxicity was evaluated using the BSLT method with Artemia salina larvae. The IC₅₀ values of the ethyl acetate and dichloromethane fractions were 4.13 µg/mL and 26.19 µg/mL (both very strong), respectively, while the LC₅₀ values were 1152.99 µg/mL (non-toxic) and 686.61 µg/mL (moderate), respectively. Both fractions demonstrated very strong antioxidant activity, with the ethyl acetate fraction exhibiting greater potential and being non-toxic, whereas the dichloromethane fraction showed moderate toxicity.